Staff experiences of a new tool for comprehensive geriatric assessment in primary care (PASTEL): a focus group study: Primary care staff experiences of geriatric assessment - Nord, Magnus; Östgren, Carl Johan; Marcusson, Jan; Johansson, Maria (Scandinavian journal of primary health care, 2020)
Objective: Comprehensive geriatric assessment (CGA) is recommended for the management of frailty. Little is known about professionals' experiences of CGA; therefore we wanted to investigate the experiences of staff in primary care using a new CGA tool: the Primary care Assessment Tool for Elderly (PASTEL). Design: Focus group interviews. Manifest qualitative content analysis. Setting: Nine primary health care centres in Sweden that participated in a CGA intervention. These centres represent urban as well as rural areas. Subjects: Nine nurses, five GPs and one pharmacist were divided into three focus groups. Main outcome measures: Participants' experiences of conducting CGA with PASTEL. Results: The analysis resulted in four main categories. A valuable tool for selected patients: The participants considered the assessment tool to be feasible and valuable. They stated that having enough time for the assessment interview was essential but views about the ideal patient for assessment were divided. Creating conditions for dialogue: The process of adapting the assessment to the individual and create conditions for dialogue was recognised as important. Managing in-depth conversations: In-depth conversations turned out to be an important component of the assessment. Patients were eager to share their stories, but talking about the future or the end of life was demanding. The winding road of actions and teamwork: PASTEL was regarded as a good preparation tool for care planning and a means of support for identifying appropriate actions to manage frailty but there were challenges to implement these actions and to obtain good teamwork. Conclusion: The participants reported that PASTEL, a tool for CGA, gave a holistic picture of the older person and was helpful in care planning. Key points To manage frailty using comprehensive geriatric assessment (CGA) in primary care, there is a need for tools that are efficient, user-friendly and which support patient involvement and teamwork *This study found that the Primary care Assessment tool for Elderly (PASTEL) is regarded as both valuable and feasible by primary care professionals *Use of carefully selected items in the tool and allowing enough time for dialogue may enhance patient-centeredness *The PASTEL tool supports the process of identifying actions to manage frailty in older adults. Teamwork related to the tool and CGA in primary care needs to be further investigated and developed